Visualizing Quranic Words With Parallel Plot - Yuso, R.J.R.; Zainuddin, R.; Baba, M.S.; Jomhari, N.; Yusoff, Z.M. (2012)
Parallel plot is a relatively new type of plot in comparison to scatter plot. The aim of this paper is to find out the effectiveness of parallel plot visualization in comparison to the scatter plot for novice users. Comparison through literature shows that parallel and scatter plot visualization techniques offer similar visualization features. A study was conducted based on the parallel plot in Parallel Coordinate for the Qur'an (PaCQ) interface using a relational model, Goals Operators Methods and Selection Rules (GOMS) analysis and user performance evaluation. Based on the GOMS analysis, the subtasks and operation time involved in exploring data in scatter plot exceeds the subtasks and operation time in parallel plot in relation to the PaCQ interface developed for novice user even though, earlier studies found that scatter plot is easier to use. The GOMS analysis shows that the average time taken to complete tasks for the parallel plot is shorter then the scatter plot. A user performance evaluation shows no significant difference in the scores of interpreting the parallel plot within three levels of educational level of novice users. These findings provide evidences that the parallel plot is more effective for PaCQ designed for novice users.